The Primacy of a Decision Taken in a Local Referendum over a Contract Concluded by Local Self-Government Bodies: the Example of the Czech Republic - Kudrna, Jan (PRAWO i WIĘŹ, 2025)
A well-functioning local self-government provides the greatest scope - given the proximity of its members to their elected representatives and the proximity of both groups to the issues - for the realisation of its members' political rights and their ideas about the governance of the area. In many ways, local governments are "laboratories" of the representative system and democracy. They provide direct opportunities for the expression of different views and positions. If the legal system of a country allows for direct instruments of democracy at the local level, as in the Czech Republic, then there is room for a direct conflict between the interests and intentions promoted by elected representatives and the ideas of their constituents. The result can be a legal problem as to which decision is legally preferable, especially if the decision of the elected bodies is enshrined in a binding legal contract. This question has arisen repeatedly in the Czech Republic, until the Constitutional Court of the Czech Republic ruled in a series of decisions that there is no such thing as a "perpetual contract" and that a concluded contract cannot be an obstacle to holding a local referendum.